Выбор страноведческих тем и содержания урока при обучении английскому языку как второй специальности на i-ii курсах педагогических университетов (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2008)
The article deals with the choice of topics and country studies material in the English language teaching process at junior courses of university philology departments. Some didactical methods concerning intercultural factors which should be taken into account are mentioned.